HUBUNGAN TINGKAT KEPATUHAN PASIEN CHRONIC KIDNEY DISEASE STAGE V DALAM MENJALANI TERAPI HEMODIALISIS DENGAN KUALITAS HIDUP PASIEN - Dewi, Putu Yanita Rosintya; Sutresna, I Nyoman; Kio, Alfiery Leda (Media Keperawatan:Politeknik Kesehatan Makassar, 2021)
Compliance with chronic kidney disease stage V patients undergoing hemodialysis is important to maintain body homeostasis. Quality of life is an important indicator for assessing the effectiveness of hemodialysis, so it is an important goal in the treatment of end-stage renal disease. This study purposed to determine the correlation between the level of patients' compliance with chronic kidney disease stage V in undergoing hemodialysis therapy and the patient's quality of life. The correlation study design, with a cross-sectional approach. The total of samples is 110 respondents. The sampling technique used was nonprobability sampling, namely purposive sampling. The results of the analysis showed that the level of patient compliance was 90% in the adherent category. The quality of life of patients was 78.2% with the good category. It was concluded that there was a correlation between the level of compliance in undergoing hemodialysis therapy with the patient's quality of life. It is suggested to the service provider to increase compliance with hemodialysis.